DIGITALISASI SKRIPSI DALAM REPOSITORI PROGRAM STUDI MANAJEMEN SUMBERDAYA PERAIRAN FAKULTAS PERIKANAN DAN ILMU KELAUTAN UNIVERSITAS PATTIMURA: Digitalization Thesis To Repository Aquatic Resources Management Study Program Faculty Fisheries And Marine Science Pattimura University - Nur Tasmiah Sirajuddin; Yuliana Natan; Martha L. Wattimena; Sophia N. M. Fendjalang; Krisye; Rahman (Pakis Journal Institute, 2023)
Thesis is one of the references used as a reference to writing a scientific work in an academic environment both by students and lecturers in carrying out research assignments. Existing thesis can be a source of research ideas, information on student research interests and ongoing research development. These benefits become more optimal with the ease of accessing thesis data anytime and anywhere. The aim of this activity is to create a digital-based thesis in a repository at the Study Program in Aquatic Resources Management at Pattimura University. This activity was carried out in October - November 2022. The stages of the activity included coordination, collecting thesis softcopy data, inputting thesis data into Google Drive and the website in the form of a repository, making posters as a medium for outreach to students and lecturers and evaluating the effectiveness of the repository on the website. The results of this activity can be concluded that digitizing thesis into a repository can provide easy access anytime and anywhere for both students and lecturers who need information related to thesis data in the Aquatic Resources Management Study Program.